Penggunaan Model Prototype dalam Membuat Library System di SMPIT AL Mustopa - Achmad Udin Zailani; Agung Perdananto; Maulana Ardhiansyah (SMARTICS Journal, 2020)
The library in its management is still not well-database so that the data managers carried out at the library of SMPIT AL Mustopa have not been systematic and still use the old-fashioned way of recording student data so that it results in frequent data collection errors that include lending, book returns, delays and fines. With the old way system causes users to spend a long time to borrow books. So this research will complement those shortcomings by making a computerized Library System using the PHP programming language and Mysql database and so use the Prototype model test technique. Application development uses a prototype approach that can help customers and system developers explore the specifications of the system requirements as desired by the customer. The findings of this study are computerized web-based library systems between book data and users so as to facilitate the performance of agencies in providing information, processing data and computerized library reporting that is easily maintained and developed and helps minimize errors in processing library data